A comprehensive review of renewable and sustainable biosourced carbon through pyrolysis in biocomposites uses: Current development and future opportunity. (December 2021) - Chang, Boon Peng; Rodriguez-Uribe, Arturo; Mohanty, Amar K.; Misra, Manjusri
Abstract: Highly order-structured carbon-based materials such as graphite, graphene, and carbon nanotubes hold promise in delivering the next generation of carbon-based advanced composite materials due to their superior performance in many applications. Recently, partially graphitic biosourced carbon (BioC) has shown to be a new, sustainable, inexpensive and practical alternative carbonaceous functional filler for polymer and biocomposite development (i.e. thermoplastic, thermoset, elastomer and foam). The thermochemical conversion of different types of biomass in a limited oxygen environment (pyrolysis) can be controlled and optimized to produce engineered BioCs with tunable surface area, morphology, polarity, porosity, intrinsic modulus and carbon content, which are being explored in different applications. Renewable BioCs exhibit variable surface chemistry that can be further modified to achieve better compatibility with polymers. BioC can be used as a reinforcing agent and as a multi-functional filler (e.g. electrical conductivity, antimicrobial, fire retardant, etc.) for polymer composite uses, which opens a new generation of biobased composite materials in the commercial market. This article provides an in-depth review of the current state-of-the-art fabrication, characterization, and performance of the BioC-based biocomposites. Further, the effect of the different synthesized BioCs on the polymers' behavior and performance are reviewed in-depth. Finally, the challenges and future perspectives for these BioC-based biocomposites are discussed. Highlights: Sustainable biosourced carbons (BioC) for composite applications were reviewed. Tuning the pyrolysis conditions produced BioC with varying key functionalities. Highly graphitic engineered BioC provides substantial boost in composite modulus. BioC exhibited great potential to replace mineral fillers and carbon blacks in biocomposites uses.